A Rare Case of Dedifferentiated Solitary Fibrous Tumor. (28th October 2020) - Kanteti, A P; Martinez Duarte, E
Abstract: Casestudy : Dedifferentiated solitary fibrous tumor is a rare malignant subtype of the common benign mesenchymal neoplasm with fibroblastic differentiation known as solitary fibrous tumor (SFT). These account for less than 2% of all soft masses; and about 20% of SFTs turn aggressive. They feature bland spindle cells creating a classic "pattern-less pattern" in collagenous stroma with prominent staghorn vessels. They can dedifferentiate into a biphasic tumor with low grade areas that are spindle cell rich and high-grade areas with epithelioid cells, mitotic figures and necrosis. Here we present an 84-year-old female who came from an outside institution for a pathology review. The patient's clinical history was lacking and biopsies from the right lower and middle lobes of the lung, azygous and hilar lymph nodes were investigated. The pathology revealed multiple areas with epithelioid cells that were pleomorphic and had high nuclear to cytoplasmic ratio. These areas also contained numerous mitotic figures, necrosis and giant cells; with lymphovascular space invasion. There was a clear demarcation between the epithelioid area and an area rich in spindle cells. The spindled areas revealed a fascicular architecture with intervening sclerotic stoma and prominent rounded and dilated blood vessels. Immunohistochemistry analysis of the epithelioid and spindle cell areas were positive for STAT6. Additional testing for CD34 was diffusely positive in the spindle cell component and only focally positive in the high-grade portion of the tumor. Ki-67stain was utilized to estimate the proliferative index which was up to 80 percent in the high-grade epithelioid component and about 15% in the spindle cell portion. These morphological and histochemical findings were consistent with the diagnosis of a dedifferentiated solitary fibrous tumor.